2019
DOI: 10.1016/j.eurox.2019.100042
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic excision of the cervix in women over 40 years with human papilloma virus persistency and normal cytology

Abstract: Objective Persistent infection with human papillomavirus (HPV) is recognized as the main risk factor of cervical cancer. Investigation via cytology and colposcopy have lower sensitivity than HPV testing in the diagnosis of high-grade cervical intraepithelial neoplasia (CIN2+). Despite normal cytology and colposcopy findings women with persistent HPV infection have an increased risk of CIN2+. The aim of the study was to evaluate the proportion of histologically confirmed CIN2+ in women with persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The routine for follow up of HPV-related CIN 1 or HPV persistence with or without dysplasia is with a new HPV test and cytology or colposcopy with biopsies. In a recent study from Uppsala, diagnostic conization showed a high frequency of dysplasia in HPV-positive women, where 15% (6/40) of women older than 40 years of age, were revealed to have an undiagnosed CIN2+ when LEEP was performed [25].…”
Section: Plos Onementioning
confidence: 95%
“…The routine for follow up of HPV-related CIN 1 or HPV persistence with or without dysplasia is with a new HPV test and cytology or colposcopy with biopsies. In a recent study from Uppsala, diagnostic conization showed a high frequency of dysplasia in HPV-positive women, where 15% (6/40) of women older than 40 years of age, were revealed to have an undiagnosed CIN2+ when LEEP was performed [25].…”
Section: Plos Onementioning
confidence: 95%
“…Even if HSIL or cervical cancer were not found in this study, it is impossible to ensure that neither were present, since the transformation zone was not visible during the colposcopy, and biopsies were randomly collected. A recent study showed that a persistent HPV infection needs to be monitored despite benign cytology and colposcopy, since 6/19 (32%) women with a persistent and ongoing HPV infection were revealed to have an undiagnosed CIN2 + when LEEP was performed [ 32 ]. The PPV is an indicator of the significance of having a persistent HPV infection for the risk to have dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Another weakness is that there was no data on sexual partners during the last 5 years which could have explained some of the cases with HPV positivity. Finally, the histological data were obtained by, in many cases, randomly collected cervical biopsies, which means that there might have been HSIL or cervical cancer in the invisible part of the cervix, in analogy with what has been seen in the study by Aarnio et al [ 32 ]. In these cases, it might have been advisable to perform diagnostic conization.…”
Section: Discussionmentioning
confidence: 99%
“…Even if HSIL or cervical cancer were not found in this study it is impossible to ensure that neither were present, since the transformation zone was not visible during the colposcopy, and biopsies were randomly collected. A recent study showed that a persistent HPV infection needs to be monitored despite benign cytology and colposcopy, since 6/19 (32%) women with a persistent and ongoing HPV infection were revealed to have an undiagnosed CIN2+ when LEEP was performed (33). The PPV is an indicator of the signi cance of having a persistent HPV infection for the risk to have dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Another weakness is that there was no data on sexual partners during the last 5 years which could have explained some of the cases with HPV positivity. Finally, the histological data were obtained by, in many cases, randomly collected cervical biopsies, which means that there might have been HSIL or cervical cancer in the invisible part of the cervix, in analogy with what has been seen in the study by Aarnio et al (33). In these cases, it might have been advisable to perform diagnostic conization.…”
Section: Discussionmentioning
confidence: 99%